Determinants of Business Risk in Pandemi Era - Suharti, Eni; Fadli, Ahmad; Zatira, Dhea; Hakim, Zulman (Dinasti International Journal of Economics, Finance & Accounting, 2023)
To determine the effect of investment decisions, funding decisions and company size on business risk in hotel, restaurant and inn division companies recorded on the Indonesia Stock Trade, the period utilized in this think about is 5 (five) a long time, beginning from 2017 -2021. This think about employments a quantitative approach. The populace in this think about is 35 companies in the hotel, restaurant and hotel sector which are still recorded on the Indonesia Stock Trade for the period 2017 - 2021. The sampling technique used was purposive sampling and a sample of 12 companies was obtained. The information examination method utilized is board information relapse examination with the assistance of the Eviews 9 and SPSS programs. The results of the study show that investment decisions have no effect on business risk and are not significant. Funding decisions have a positive and significant effect on business risk and company size has no effect on business risk and is not significant on business risk. Simultaneously investment decisions, funding decisions and company size have a positive and significant effect on business risk in the 2017-2021 period.